A Comparison between splenic fossa and subhepatic fossa auxiliary partial heterotopic liver transplantation in a porcine model. Issue 6 (June 2016) - Ai, Lemin; Liang, Xiao; Wang, Zhifei; Shen, Jie; Yu, Feiyan; Xie, Limei; Pan, Yongming; Lin, Hui
Abstract : To test the alternative possible locations for the placement of a liver graft and the relevant surgical technique issues, we developed a porcine model of auxiliary partial heterotopic liver transplantation (APHLT) and evaluated the difference between 2 styles of liver transplantation, either subhepatic fossa or splenic fossa APHLT, by comparing survival and biochemical indexes. Thirty‐eight miniature pigs were randomly divided into 2 groups. A left hemihepatic graft without the middle hepatic vein (HV) was procured from the living donor. In group A (n = 9), an 8 mm diameter polytetrafluoroethylene (PTFE) graft approximately 2.5 cm long was connected to the left HV while another PTFE graft of the same size was connected to the left portal vein (PV). The liver graft was implanted in the right subhepatic fossa following splenectomy and right nephrectomy. In group B (n = 10), a PTFE graft of the same size was connected to the left HV while the liver graft was implanted in the splenic fossa following splenectomy and left nephrectomy. Survival rate and complications were observed at 2 weeks after transplantation. Data were collected from 5 animals in group A and 6 animals in group B that survived longer than 2 weeks. The liver function and renal function of the recipients returned to normal at 1 week after surgery in both groups. Eighty‐eight percent (14/16) of the PTFE grafts remained patent at 2 weeks after surgery, but 44% of the PTFE grafts (7/16) developed mural thrombus. No significant differences in the survival rate and biochemistry were found between the 2 groups. In conclusion, the splenic fossa APHLT can achieve beneficial outcomes similar to the subhepatic fossa APHLT in miniature pigs, although it also has a high morbidity rate due to hepatic artery thrombosis, PV thrombosis, and PTEF graft mural thrombus formation. Liver Transplantation 22 812–821 2016 AASLD .